The mysteries of the Bible collection. 7 [videorecording (DVD)] - Kiley, Richard; Simmons, Jean, 1929-2010 (A & E Home Video : Distributed by New Video, 2007)
An exploration of the facts behind the Bible stories. Included are discussions with scholars, archaeologists, and scientists and visits to historic sites.